Burnham Breaker - Greene, Homer, 1853-1940 (Salt Lake City, UT : Project Gutenberg, 2003)
"Burnham Breaker" by Homer Greene is a novel written in the late 19th century. The story unfolds in the backdrop of Scranton, Pennsylvania, a city entrenched in the coal-mining industry, and follows the lives of young boys toiling under harsh conditions, particularly highlighting the character of Ralph. Ralph, who yearns for a sense of belonging and searches for his identity, becomes entwined with Robert Burnham, the compassionate manager, whose kindness touches the lives of those working under him. The opening of "Burnham Breaker" sets up a vivid portrayal of the coal breaker where boys work long hours, picking slate from coal, while dreaming of freedom and a better life outside their prison-like environment. On a significant day, which happens to be circus day, the screen-room boys find their mundane toil interrupted when Burnham rewards their loyalty by granting them time off to visit the circus. This gesture highlights Burnham's compassion and foreshadows the deeper connections that will unravel between him and Ralph, especially as Ralph's past comes to light, revealing his lack of identity and longing for family. The narrative begins to weave themes of identity, loss, and the struggles of the working class in an industrial society. (This is an automatically generated summary.)
Release date is 2003-12-01
E-text prepared by Charles Aldarondo, Keren Vergon, William Flis, and the Project Gutenberg Online Distributed Proofreading Team. Special thanks to Mike Greene and the Little Greene Schoolhouse (http://www.users.nac.net/mgreene/Homer_Greene_Museum.html) for supplying missing pages for this rare book
Keywords: Boys -- Juvenile fiction; Foundlings -- Juvenile fiction; Coal mines and mining -- Juvenile fiction; Scranton (Pa.) -- Juvenile fiction